1991
DOI: 10.1136/bmj.303.6795.173
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trials in single subjects. 1. Value in clinical medicine.

Abstract: Randomised controlled group trials are the gold standard in clinical research and provide information about the average effect of a treatment in a target population. Such information, however, cannot necessarily be transferred to a single patient because finding a significant effect of treatment does not mean that all the study subjects responded. Besides, in real life clinicians are often confronted with vague symptoms and poorly defined diseases; this is a different case from the strict criteria used in scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…These common problems lead to huge numbers of encounters between patients and physicians. Despite this and despite endorsements of the technique25 26 27 28 29 30 31 n of 1 trials are rarely used. This is probably because of the extra effort they demand from patients and physicians—which could be justified if randomised studies showed that n of 1 trials result in clinically important benefits over standard practice.…”
Section: Discussionmentioning
confidence: 99%
“…These common problems lead to huge numbers of encounters between patients and physicians. Despite this and despite endorsements of the technique25 26 27 28 29 30 31 n of 1 trials are rarely used. This is probably because of the extra effort they demand from patients and physicians—which could be justified if randomised studies showed that n of 1 trials result in clinically important benefits over standard practice.…”
Section: Discussionmentioning
confidence: 99%
“…N-of-1 trials compare different interventions given in random order within a single patient (Fleming 1982;Johannessen 1991;Zucker et al 1997). In order to make more general conclusions, a series of n-of-1 trials may be conducted to defi ne trends (Zucker et al 2010).…”
Section: Sample Size and Demonstration Of Superiority For Market Apprmentioning
confidence: 99%
“…This randomized, double-blind, placebo-controlled trial employed a novel study design and statistical methodology: serial N-of-1 trials analysed using Bayesian statistical modeling. Traditionally, N-of-1 trials have been used to evaluate the effectiveness of an intervention in individual patients [13]. We adapted a statistical technique published by Zucker et al which allows for the combination of data from multiple N-of-1 trials to obtain an estimate of treatment effectiveness for a population [23].…”
Section: Introductionmentioning
confidence: 99%